Applied International Finance - O'Brien, Thomas J (Business Expert Press, 2014)
Ebook from IG Library ; This text is designed for use in a course in an applied international corporate finance for managers and executives. Instead of the encyclopedic approach, the text focuses on the two main issues of interest to managers who deal with overseas operations. The first main issue is how uncertain foreign exchange (FX) rate changes affect a firm's ongoing cash flows and equity value, and what can be done about that risk. The second main issue is the estimation of the cost of capital for international operations and the evaluation of overseas investment proposals. Numerous examples of real world companies are used. The text is divided into two parts based on the two main issues. Each part includes a case that unifies the ideas. In Part I, the case company has overseas operations and is faced with ongoing FX exposure in corporate revenues. The decision-maker estimates the FX exposure and considers financial hedging using foreign currency debt and currency swaps. The accounting implications are also considered. In Part II, the case company evaluates a proposal to expand production for a foreign market, with location alternatives being the home country, the foreign market country, or a cheap-labor emerging market country.